CD44v8-10 mRNA contained in serum exosomes as a diagnostic marker for docetaxel resistance in prostate cancer patients. Issue 7 (July 2020) - Kato, Taku; Mizutani, Kosuke; Kawakami, Kyojiro; Fujita, Yasunori; Ehara, Hidetoshi; Ito, Masafumi
Abstract: Background: Docetaxel is first-line chemotherapy for castration-resistant prostate cancer (CRPC), but most patients acquire docetaxel resistance. CD44 has been shown to be involved in drug resistance of cancers including prostate cancer. We hypothesized that CD44 in serum exosomes could be a diagnostic marker for docetaxel resistance in CRPC patients. In this study, we examined CD44 protein and mRNA expression in cell lysates and exosomes isolated from prostate cancer cells, evaluated the effect of CD44v8-10 knockdown on docetaxel sensitivity and measured CD44 mRNA copy numbers contained in serum exosomes in prostate cancer patients. Materials and methods: Docetaxel-sensitive PC-3 prostate cancer cells and docetaxel-resistant PC-3R cells established previously from parental PC-3 cells were used. CD44v8-10 knockdown was performed by siRNA transfection. Blood was collected from 50 docetaxel-naïve and 10 docetaxel-resistant patients and 15 control males. CD44 protein expression was evaluated by Western blotting. CD44 mRNA expression was measured by RT-digital PCR. Results: The levels of CD44v8-10 protein and mRNA in cell lysates and exosomes were higher in PC-3R cells than in PC-3 cells. CD44v8-10 knockdown significantly increased docetaxel sensitivity of PC-3R cells. The CD44v8-10 mRNA copy numbers in serum exosomes were higher in docetaxel-resistant patients than in docetaxel-naïve patients and control males (median 46, 12 and 17 copies/mL serum, respectively, P = 0.032). In contrast, the serum exosomal mRNA copy numbers of CD44 standard isoform (CD44s) were not different among 3 groups (median 25, 14 and 13 copies/mL serum, respectively, P = 0.150). Conclusions: CD44v8-10 may be involved in docetaxel resistance in prostate cancer and serum exosomal CD44v8-10 mRNA could be a diagnostic marker for docetaxel-resistant CRPC. Abstract : Cell biology; Molecular biology; Cancer research; Chemotherapy; Urology; Castration-resistant prostate cancer, CD44, Docetaxel resistance, Exosomes, Diagnostic marker